2022
DOI: 10.1177/0271678x221076568
|View full text |Cite
|
Sign up to set email alerts
|

Increased capillary stalling is associated with endothelial glycocalyx loss in subcortical vascular dementia

Abstract: Proper regulation and patency of cerebral microcirculation are crucial for maintaining a healthy brain. Capillary stalling, i.e., the brief interruption of microcirculation has been observed in the normal brain and several diseases related to microcirculation. We hypothesized that endothelial glycocalyx, which is located on the luminal side of the vascular endothelium and involved in cell-to-cell interaction regulation in peripheral organs, is also related to cerebral capillary stalling. We measured capillary … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 86 publications
(108 reference statements)
1
15
0
Order By: Relevance
“…Previous studies have shown that the endothelial glycocalyx is degraded in diseases, leading to increased leukocyte adhesion ( Kumase et al, 2010 ; Schmidt et al, 2012 ; McDonald et al, 2016 ). Furthermore, the decreased extent of the cerebral endothelial glycocalyx is associated with increased capillary stalling ( Yoon et al, 2022 ). RNA-seq results also suggested that leukocyte-endothelial cell interaction could be enhanced in pericyte-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that the endothelial glycocalyx is degraded in diseases, leading to increased leukocyte adhesion ( Kumase et al, 2010 ; Schmidt et al, 2012 ; McDonald et al, 2016 ). Furthermore, the decreased extent of the cerebral endothelial glycocalyx is associated with increased capillary stalling ( Yoon et al, 2022 ). RNA-seq results also suggested that leukocyte-endothelial cell interaction could be enhanced in pericyte-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…Body temperature was maintained at 36.5–37.5°C with the use of a heating pad and a rectal feedback probe (Harvard Apparatus, 55-7020). Our procedures for OCTA data analysis have been described previously ( Yoon et al, 2022 ). Maximum intensity projection of 3D OCT angiograms was performed in a depth direction over 150–300 μm below the cortical surface.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the healthy murine brain, circulating leukocytes stall transiently in 0.4% of cerebral capillaries, possibly by interacting with the glycocalyx or selectins on ECs 128 , 172 174 ( Fig. 4 ).…”
Section: Immune Cell Control Of Blood Supply To the Cnsmentioning
confidence: 99%